A systematic review and meta-analysis on the co-infection of Helicobacter pylori with intestinal parasites: public health issue or neglected correlation?. Issue 4 (3rd April 2022) - Taghipour, Ali; Bahadory, Saeed; Badri, Milad; Yadegar, Abbas; Mirsamadi, Elnaz Sadat; Mirjalali, Hamed; Zali, Mohammad Reza
ABSTRACT: The current study was conducted to assess the prevalence and odds ratio (OR) of co-infection of Helicobacter pylori ( H. pylori ) and intestinal parasites (IPs). English databases were searched. A total of 18 studies including 14 studies with cross-sectional design (a total of 3739 participants) and 4 studies with case-control design (397 patients and 320 controls) met the eligibility criteria. The pooled prevalence of H. pylori, intestinal parasite infections (IPIs), and their co-infections in different populations were 48.3% (95% CI, 34.1–62.8%), 15.4% (95% CI, 10–22.8%), and 11% (95% CI, 6.7–17.6%), respectively. The co-infection of H. pylori and Giardia was 7.6% (95% CI, 4.9–11.7%). Although statistically not significant, the risk of co-infection of H. pylori and IPIs was higher in case group compared to control group (OR, 1.59; 95% CI, 0.77–3.25). The overlaps between H. pylori and IPIs in countries with lower human development index (HDI) and income levels were high.